An exploration on process of change in men's parallel bar skills - Yang, T.-S. (Korean Journal of Sport Science, 2021)
Purpose: The purpose of this study is to explore the process of change in parallel bar Skills over the last 20 years and to suggest the Skills to learn. Methods: This study targeted on 48 finalists in parallel bar from 5 Olympic Games from 2000 to 2016 and 2019 World Championship over the last 20 years and explored the process of change in difficulty elements, each element group, and salto and arm hang. Results: First, Element Group I preferred healy to support the most and performed it for 41 times. Also, percentage of salto and arm hang got lower and got substituted by Swing forward with 3/4turn and 3/4 healy to support and following a swing element to handstand on 1 rail, Healy to support. Secondly, Element Group III performed underswing frequently while performing salto and arm hang less frequently. Element Group III changed their skills to Moy piked with straddle backward to handstand, Swing forward straddle cut backward, and regrasp with straight body at horizontal. Third, Element Group IV preferred double salto backward pike the most in the past. However, the skill changed to double salto forward tuck with 1/2turn starting from 2016 Olympics. Conclusions: Parallel bar is regarded as a weak gymnastics event. In response, this study result is expected to be used as the base data for growing the strength in parallel bar and winning the medals in main international competitions by suggesting the parallel bar Skills that Korean athletes need to learn.